Healthcare-Associated Infections in Subjects With Severe Acquired Brain Injury: The Effect of Microbial Colonization on the Functional Outcome. Data From a Multicenter Observational Study - Bartolo, Michelangelo; Zucchella, Chiara; Aabid, Hend; Valoriani, Beatrice; Mancuso, Mauro; Intiso, Domenico (Frontiers in Neurology, 2020)
Background. Hospital acquired infections (HAIs) and microbial colonization are a worldwide serious threat for human health. Neurological patients with infections who undergo rehabilitation have a significantly poor recovery. The effect of microbial colonization on the functional outcome in severe acquired brain injury (sABI) subjects is still unclear. Aim. The aim of this multicenter observational study was to describe the clinical impact of HAIs and colonization on the functional outcome of sABI subjects admitted to inpatient neurorehabilitation. Methods. Patients were assigned to 3 groups: infected (INF), not infected (noINF), and colonized (COL). The Glasgow Coma Scale (GCS), The Rancho Los Amigos Levels of Cognitive Functioning Scale (LCF), Disability Rating Scale (DRS) and modified Barthel Index (mBI) assessments were performed both at admission and discharge. Results. Two hundred sixty-five (92F/173M) patients were enrolled: 134 were assigned to the Infected group (INF), 63 to the Colonized group (COL) and 68 to the no-Infected group (noINF). In the INF group, 231 culture specimens were found positive for bloodstream (44.2%), respiratory tract (25.5%), urinary tract (18.6%), gastro-intestinal tract (8.3%), skin (3%) and cerebrospinal fluid (0.4%) infections. After rehabilitation, all groups showed a significant improvement in all assessment tests, except for the noINF group that did not show any improvement in GCS. Both noINF and COL groups showed a significantly higher gain in mBI than the INF group (p = 0.000). The COL group showed a significantly higher gain than the noINF group in GCS (p = 0.001). A significantly lower improvement was detected in the INF group than the COL and noINF groups. The rate of patients who needed functional isolation was higher in the INF group than the COL group. Length of Stay (LOS) (days) was 56 ± 50.7; 88.3 ± 55; and 101.3 ± 73.6 for noINF, INF and COL groups, respectively. The number of deaths in the INF group was significantly higher (24.6%) than the noINF group (7.4%) and comparable to the COL group (19%). Conclusion. Colonized sABI patients obtained a similar functional outcome to that of subjects who had no infections, even if they needed a significantly higher LOS.